Fundamentals of polymer physics and molecular biophysics - Bohidar, Himadri B. (Cambridge University Press, 2015)
"Provides a physical interpretation of the data obtained in macromolecular transport phenomena in a given system and also addresses some important issues and concepts related to biopolymers such as proteins and nucleic acids"--Resumé vydavatele.
Keywords: polymery; fyzika polymerů; molekulární biofyzika; polymers; physics of polymers; molecular biophysics; příručky; handbooks, manuals, etc